2017
DOI: 10.4317/medoral.21949
|View full text |Cite
|
Sign up to set email alerts
|

Histological differences in the adherence of connective tissue to laser-treated abutments and standard abutments for dental implants. An experimental pilot study in humans

Abstract: BackgroundThe goal of the current study is to assess the difference in connective tissue adherence to laser microtextured versus machined titanium abutments.Material and MethodsSix patients were selected and each of them received 2 implants, one combined with a laser treated abutment and one with a machined abutment. After three months, the abutments were retrieved together with their surrounding gingival tissue for histological analysis. Qualitative and quantitative evaluation of microscopical images was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
7
0
4
Order By: Relevance
“…Histological studies in animals and humans provided evidence of reattachment of the connective tissue when a laser-microgrooved healing abutment was replaced with another laser-microgrooved healing or definitive abutment [ 19 , 21 , 23 ]. In this context, in the MS group of the current study, PD showed a statistically significant increase during the restorative phase (between T0 and T1), while in the LMS group, it remained mostly constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological studies in animals and humans provided evidence of reattachment of the connective tissue when a laser-microgrooved healing abutment was replaced with another laser-microgrooved healing or definitive abutment [ 19 , 21 , 23 ]. In this context, in the MS group of the current study, PD showed a statistically significant increase during the restorative phase (between T0 and T1), while in the LMS group, it remained mostly constant.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment helps stabilize the peri-implant soft tissue and protect the peri-implant marginal bone. It has been also histologically documented in animal and human models that the peri-implant soft tissue seal developed using an 8-μm LMS on healing abutments can be transferred to another abutment with the same macro and micro-architecture [ 21 23 ]. A clinical question, however, remains unanswered: whether repeated removal and reattachment of LMS healing abutments for impression procedures and metal framework try-in disturbs and disrupts the mucosal seal.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent peri-implant inflammation, recent studies focused on a distinctive laser-generated microgrooved surface (LMS) in the cervical region of implants and titanium abutments. These surfaces might seal the implant against infections by building a strong connective tissue adherence and could therefore show less inflammatory activity and consequently a decrease in marginal bone loss in comparison with other abutment surfaces [20][21][22][23]. LMS surface is a highly orientated microgeometry produced by using a computer-controlled laser system.…”
Section: Introductionmentioning
confidence: 99%
“…Tras estudiar estas evidencias en implantes, los autores publicamos un estudio clínico en humanos más reciente, donde evaluamos las diferencias histológicas entre los tejidos blandos alrededor de pilares lisos y pilares tratados con láser en su zona cervical (23) . En el estudio encontramos diferencias estadísticamente significativas entre el porcentaje de unión existente entre el grupo de pilares tratados con láser y el grupo de pilares sin tratamiento; y llegamos a la conclusión principal de que el tejido conectivo tiene una mejor adhesión a los pilares tratados con láser en comparación a los pilares lisos.…”
Section: Introductionunclassified
“…b) Pilar de superficie lisa. Fotografías tomadas de las muestras histológicas del estudio clínico de Blázquez-Hinarejos et al (23). .…”
unclassified